Left atrial coupling index versus left atrial function index in heart failure with reduced ejection fraction and iron deficiency. (14th October 2021) - Tsarouchas, A; Bakogiannis, C; Mouselimis, D; Pagourelias, E.D; Kelemanis, I; Boulmpou, A; Vergopoulos, S; Vassilikou, A; Tzikas, S; Fragakis, N; Papadopoulos, C.E; Vassilikos, V.P
Abstract: Background: Left atrial (LA) form and function has been the focus of extensive research in heart failure with reduced ejection fraction (HFrEF). The LA coupling index (LACI, see Picture 1 for definition) and the LA function Index (LAFI) have both been proposed as potent predictors of morbidity and mortality in HFrEF. Albeit promising, both parameters have drawbacks that could limit their usefulness in clinical settings - LACI can only be measured during sinus rhythm (SR), while LAFI calculation is arguably more involved. A side-by-side comparison of the two indices has not yet been performed. Purpose: Investigate and compare the feasibility and efficacy of using LACI and LAFI as prognostic factors in HFrEF. Methods: HFrEF patients that visited our outpatient HF clinic were invited to participate in the study. Clinical examination, 6-minute walk testing, and a full echocardiographic study were performed, the latter enabling quantification of LACI, LAFI, as well as most traditional echocardiographic predictors of HF prognosis (Picture 1). LACI and LAFI cut-offs of 6 and 25 respectively were defined in accordance with the relevant literature. Cox regression was performed to assess each parameter's correlation with risk of HF-related hospitalization and mortality over a 6-month follow-up period. Results: In the end, 63 patients were included in the study (aged 69.3±9.7 years, 84% male). LACI could not be measured in 19 patients due to atrial tachycardia. The median LACI was 6.2 (8.7) while the median LAFI of the entire sample was 24.8 (44.5). LACI and LAFI correlated strongly (r=−0.813, p<0.001). Neither correlated significantly with the risk of HF-related hospitalization (Picture 1) or death in our sample (Picture 2). 6MWD was the only parameter to independently correlate with increased risk of hospitalization (HR=0.39, p<0.001) or death (HR=0.42, p=0.02). Conclusions: The collinearity detected between LACI and LAFI indicate that both quantify similar aspects of left atrial (dys)function. That said, neither index had significant capability to predict hospitalization or death in our sample of HFrEF patients. Although a non-significant trend for higher LACI in patients with poorer prognosis was detected in our sample, it was also incalculable in 30% of patients, who were not in SR during echocardiography. Extended follow-up of an expanded sample size will enable more refined investigation of LACI's and LAFI's prognostic capacity. Funding Acknowledgement: Type of funding sources: None.